Estudo Químico de Croton muscicapa Mull Arg. (Euphorbiaceae) e Avaliação da Composição Química Volátil de Ocimum spp (Lamiaceae) - Barreto, Milena Barbosa (2008)
This work describes the phytochemical studies of Croton muscicapa Müll. Arg. (Euphorbiaceae), commonly known as “velame de cheiro” and the volatile chemical composition of the aerial parts from Ocimum gratissimum and also Ocimum sp. The phytochemical studies of exsudate of the stems from C. muscicapa allowed the isolation and characterization of five substances: one triterpene: dammaradienol and four flavonoids: retusine, pachypodol, ombuine and 3,7,4´-trimethoxykaempferol. These substances are being reported for the first time for the species in study, while the dammaradienol and ombuine are being reported for the first time for the Euphorbiaceae family. All chemical substances have their structures elucidated through spectrometric techniques: IR, MS, 1D and 2D NMR (COSY, HSQC, HMBC), as well by comparison with literature data. The antioxidant potentials of the exsudate, hexanic and ethanol extracts of the leaves and stems were analyzed by using the DPPH radical scavenger. The volatile chemical composition of the essential oils of the leaves and inflorescences from Ocimum sp and O. gratissimum were examined by GC/MS and GC/FID. The inter and intraspecific variation of the chemical components present in the essential oils was avaluated pursuing the determination of the influence of extrernal factors such as seasonal harvesting (every month from march to december 2007), daylight time harvesting (6:00am, 10:00am, 2:00pm, 6:00pm), cultivation form of Ocimum sp species (garden beds exposed to the sun light and in greenhouses) and plant part (leaves and/or inflorescences).